Field‐Aligned Currents Induced by Magnetopause Motions Under Pressure Perturbations - Boyi Wang; Xinyu Xu; Yukitoshi Nishimura; Yen‐Jung Wu; Zhonghua Xu; Primož Kajdic; De‐Sheng Han; Yi Wang; Xueshang Feng (Geophysical Research Letters)
Abstract In this work, we identified 65 auroral arcs that stretched out from the equatorward boundary of auroral oval with azimuthal extensions, and investigated their upstream triggering, by utilizing conjunctions between the THEMIS probes and the all‐sky imagers at AGO P1 and South Pole stations. The results show that the magnetopause motions induced by pressure enhancements associated with IMF discontinuities or foreshock cavities likely generate upward FACs in the closed field lines near the magnetopause. The inward and azimuthal motions of magnetopause caused equatorward‐moving auroral arcs, which extended westward or eastward, centered in the prenoon (12–13 MLT) or postnoon (9–10 MLT) sectors, respectively. The dawn‐dusk asymmetry in this distribution may be due to the contribution from foreshock activities. Furthermore, stronger compression can push the magnetopause further inward, causing FACs and the corresponding discrete auroras to be distributed over a wider region extending further in both latitude and local time.